2012
DOI: 10.1111/j.1365-2486.2012.02745.x
|View full text |Cite
|
Sign up to set email alerts
|

Simple additive effects are rare: a quantitative review of plant biomass and soil process responses to combined manipulations of CO2 and temperature

Abstract: In recent years, increased awareness of the potential interactions between rising atmospheric CO2 concentrations ([ CO2 ]) and temperature has illustrated the importance of multifactorial ecosystem manipulation experiments for validating Earth System models. To address the urgent need for increased understanding of responses in multifactorial experiments, this article synthesizes how ecosystem productivity and soil processes respond to combined warming and [ CO2 ] manipulation, and compares it with those obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
422
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 390 publications
(447 citation statements)
references
References 110 publications
20
422
5
Order By: Relevance
“…Indeed, the productivity response to experimental warming varies with soil moisture, but not in a consistent manner (Elmendorf et al., 2011, 2012; Wu et al., 2011). Other ecosystem factors, such as species composition, and environmental factors like soil type and infiltration rates (Dieleman et al., 2012; Way & Oren, 2010) are likely also important and potentially explain the inconsistent relationship between soil moisture and the response to increased temperature. Furthermore, experimental warming tends to increase productivity more strongly near the poles (Rustad, Campbell, Marion, Norby, & Mitchell, 2001), indicating another context dependency of warming effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the productivity response to experimental warming varies with soil moisture, but not in a consistent manner (Elmendorf et al., 2011, 2012; Wu et al., 2011). Other ecosystem factors, such as species composition, and environmental factors like soil type and infiltration rates (Dieleman et al., 2012; Way & Oren, 2010) are likely also important and potentially explain the inconsistent relationship between soil moisture and the response to increased temperature. Furthermore, experimental warming tends to increase productivity more strongly near the poles (Rustad, Campbell, Marion, Norby, & Mitchell, 2001), indicating another context dependency of warming effects.…”
Section: Introductionmentioning
confidence: 99%
“…We expected that warming and drying from the OTC (Liancourt et al., 2012) would negatively impact plant productivity and diversity, and especially so in the warmer, drier location, where plants might be operating closer to their thermal optima (Wertin, Reed, & Belnap, 2015), and be more water limited. As such, we would expect the drying effects of the warming treatment to be more consequential than the temperature effects (Dieleman et al., 2012). We further hypothesized that additional precipitation could moderate much of the negative impact of the OTC.…”
Section: Introductionmentioning
confidence: 99%
“…survival, growth, abundance, behaviour e.g. species diversity, biomass, total primary production additive antagonistic Crain et al [15] Darling & Côté [16] Dieleman et al [32] Gruner et al [26] Harvey et al [47] Przelawski et al [22] Wu et al [31] Stephens et al [29] Wahl et al [33] Jackson [27] Figure 4. Links between various categories of responses to multiple stressors and the types of interactions occurring between these stressors.…”
Section: Can We Predict Stressor Interaction Types?mentioning
confidence: 99%
“…Many experiments have been carried out to study the responses of plants to high [CO 2 ] at various levels ranging from the ecosystem to the genome (e.g. Ainsworth and Long 2005;Luo et al, 2006;Teng et al, 2006;Niu et al, 2011;Dieleman et al, 2012;AbdElgawad et al, 2014;Zinta et al, 2014). Such studies revealed that elevated [CO 2 ] increases plant growth and crop yield by the stimulation of carboxylation and suppression of oxygenation activity of ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) particularly in C3 plants, whereas the effects are marginal in C4 plants because Rubisco is already saturated at ambient [CO 2 ] (reviewed by Bowes 1991;Ghannoum et al, 2003;Feng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%